Cloning and characteristic prediction of 42 kda chitinase from trichoderma asperellum - Phùng, Thị Bích Hòa; Mai, Thị Thu Hiền; Nguyễn, Hoàng Tuệ; Nguyễn, Tý; Nguyễn, Thị Kim Cơ; Nguyễn, Xuân Huy (Hue University Journal of Science: Natural Science, 2021)
Chitinase is an enzyme that catalyzes the hydrolytic reaction of chitin by cleaving 1,4-N-acetyl-β-glucosaminide linkages. Chitinase has been widely used in various fields, especially pest control, pollution reduction, and basic and applied biology. Chitinase from microorganisms is an essential source, typically from Trichoderma. After removing intron sequences, the gene encoding chitinase 42 kDa (chi42) from Trichoderma asperellum SH16 was synthesized and cloned into the pUC19 vector. The gene chi42 digested by BamHI and SacI was successfully cloned into the pQE30 vector, which was expressed in E. coli. The primary in silico analysis of the protein structure shows that chitinase is an extracellular protein. The secondary structure analysis reveals that chitinase has 15 α helices and 13 β sheets, while the dimension structure of chitinase is highly homological with the chitin hydrolytic enzyme from T. harzianum. The chitinase from T. asperellum is resistant to temperatures higher than 65 °C and exhibits acidic catalysis activity. Our results would provide basic information for heterologous expression and scale-up production of chitinase 42 kDa.